Molecular Identification of Leishmania spp. in Sand Flies (Diptera: Psychodidae, Phlebotominae) From Ecuador. Issue 6 (12th July 2017) - Quiroga, Cristina; Cevallos, Varsovia; Morales, Diego; Baldeón, Manuel E; Cárdenas, Paúl; Rojas-Silva, Patricio; Ponce, Patricio
Abstract: The detection and identification of natural infections in sand flies by Leishmania protozoan species in endemic areas is a key factor in assessing the risk of leishmaniasis and in designing prevention and control measures for this infectious disease. In this study, we analyzed the Leishmania DNA using nuclear ribosomal internal transcript spacer (ITS) sequences. Parasite DNA was extracted from naturally infected, blood-fed sand flies collected in nine localities considered leishmaniasis-endemic foci in Ecuador. The species of parasites identified in sand flies were Leishmania major -like, Leishmania naiffi, Leishmania mexicana, Leishmania lainsoni, and "Leishmania sp . siamensis" . Sand fly specimens of Brumptomyia leopoldoi, Mycropigomyia cayennensis, Nyssomyia yuilli yuilli, Nyssomyia trapidoi, Pressatia triacantha, Pressatia dysponeta, Psychodopygus carrerai carrerai, Psychodopygus panamensis, and Trichophoromyia ubiquitalis were found positive for Leishmania parasite. These findings contribute to a better understanding of the epidemiology and transmission dynamics of the disease in high-risk areas of Ecuador.